Numerical prediction of sound scattering from surfaces with fractal geometry: A preliminary investigation - Bradley, David; Snow, Erik O.; Riegel, Kimberly A.; Nasipak, Zachary; Terenzi, Andrew S. (AIP, 2014)
Sound diffusive and scattering surfaces can be implemented in architectural spaces to improve the acoustical qualities of the space, particularly by attenuating the effects of harsh reflections and by producing a more diffuse sound field. These surfaces typically are effective only for a limited range of frequencies, dependent on the scale of the surface geometry. Given the broad frequency range of human hearing, an ideal diffuser would provide scattering across many frequencies. There is a direct relationship between surface roughness size and the wavelength of the scattered sound; therefore, scale-invariant fractal surfaces can be useful in achieving this ideal. In this study, virtual 1-D fractal surfaces have been generated using the Random Midpoint Displacement (RMD) algorithm. A BEM method to simulate the sound diffusive properties of these surfaces was developed and some preliminary results are presented.
161st Meeting Acoustical Society of America, 23–27 May 2011, Seattle, Washington
Keywords: Fractal surfaces; sound energy; acoustic diffuser